A Muslim Chaplaincy for Asylum Seekers? Results from an Evaluation Research Study. (June 2020) - Schmid, Hansjörg; Sheikhzadegan, Amir
Due to the high number of Muslim applicants in the Swiss asylum system, in recent years there have been calls for an introduction of a Muslim chaplaincy service into Switzerland's asylum centers. Acknowledging this need, the Swiss federal government ran a Muslim chaplaincy pilot service in Zurich's Juch Asylum Center between July 2016 and June 2017, with a view to its possible roll-out across Switzerland's federal asylum centers. This paper links methodological reflection with a presentation of key results in the evaluation of this project. Applying a mixed-method design based on the fourth-generation evaluation research, the study investigates the perspectives of the main stakeholder groups on the pilot project. The interaction with Muslim chaplains mostly led to a high degree of satisfaction among asylum seekers. The study shows there were difficulties and obstacles integrating Muslim chaplaincy into the center's inter-professional setting, although the interfaith cooperation with Christian chaplains nonetheless developed intensively. The study's methodological limitations, primarily caused by the setting of the study, are also discussed, as well as the impact the evaluation itself had on the asylum center setting.